Manipulation of pain catastrophizing: An experimental study of healthy participants - Bialosky, Joel E (Dove Medical Press, 2008)
Pain catastrophizing is associated with the pain experience; however, causation has not been established. Studies which specifically manipulate catastrophizing are necessary to establish causation. The present study enrolled 100 healthy individuals. Participants were randomly assigned to repeat a positive, neutral, or one of three catastrophizing statements during a cold pressor task (CPT). Outcome measures of pain tolerance and pain intensity were recorded. No change was noted in catastrophizing immediately following the CPT (F((1,84)) = 0.10, p = 0.75, partial η(2) < 0.01) independent of group assignment (F((4,84)) = 0.78, p = 0.54, partial η(2) = 0.04). Pain tolerance (F((4)) = 0.67, p = 0.62, partial η(2) = 0.03) and pain intensity (F((4)) = 0.73, p = 0.58, partial η(2) = 0.03) did not differ by group. This study suggests catastrophizing may be difficult to manipulate through experimental pain procedures and repetition of specific catastrophizing statements was not sufficient to change levels of catastrophizing. Additionally, pain tolerance and pain intensity did not differ by group assignment. This study has implications for future studies attempting to experimentally manipulate pain catastrophizing.